2018
DOI: 10.1002/ajb2.1123
|View full text |Cite
|
Sign up to set email alerts
|

Building the monocot tree of death: Progress and challenges emerging from the macrofossil‐rich Zingiberales

Abstract: Inclusion of eight fossil taxa expands the Zingiberales tree and helps explain the difficulty in resolving relationships. Inclusion of fossils was possible in part due to a large morphological data set built using nondestructive microcomputed tomography data. Collaboration between paleo- and neobotanists and technology such as microcomputed tomography will help to build the tree of death and ultimately improve our understanding of the evolutionary history of monocots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Our study used more taxon sampling and DNA nucleotide to increase the divergence-time estimation accuracy. Among those studies for divergence-time estimation of Musaceae [ 17 , 18 , 20 , 49 ], two fossils ( Spirematospermum chandlerae and Ensete oregonense ) were often used: Ensete oregonense , confirmed to be part of Musaceae [ 51 ] and Spirematospermum chandlerae Friis is the oldest known fossil of the Zingiberales. This study selected one more fossil ( Zingiberopsis attenuate ) and one secondary calibration point compared to other related studies [ 17 , 18 , 20 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study used more taxon sampling and DNA nucleotide to increase the divergence-time estimation accuracy. Among those studies for divergence-time estimation of Musaceae [ 17 , 18 , 20 , 49 ], two fossils ( Spirematospermum chandlerae and Ensete oregonense ) were often used: Ensete oregonense , confirmed to be part of Musaceae [ 51 ] and Spirematospermum chandlerae Friis is the oldest known fossil of the Zingiberales. This study selected one more fossil ( Zingiberopsis attenuate ) and one secondary calibration point compared to other related studies [ 17 , 18 , 20 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the estimated stem age of Zingiberaceae, that is, c. 105 (126-90) Ma, and the crown age of the family, that is, c. 68 (82-65) Ma, were compatible with fossils recorded from the late Cretaceous (Figure 1a). This suggests that using 'Musa' cardiosperma, Spirematospermum chandlerae and Tricostatocarpon silvapinedae to calibrate the stem age of the Zingiberaceae was reasonable (Smith et al, 2018). From the early to late Cretaceous, the climate of northern South America transitioned from arid to humid tropics (extension of tropical climate in Northern Gondwana) (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…Fossil seeds of Ensete and leaves of Zingiberopsis belong to the Musaceae and the Zingiberaceae, respectively. However, although Spirematospermum has been identified as a member of the Musaceae or the Zingiberaceae (Friis, 1988; Fischer et al, 2009), detailed analysis suggested that its origin should be placed in or allied to the Zingiberaceae (Chen & Smith, 2013; Benedict et al, 2015; Smith et al, 2018). Three other fossils were also assigned to the Zingiberaceae (Smith et al, 2018): Striatornata sanantoniensis and Tricostatocarpon silvapinedae found from the Campanian (83.5–72 Ma) in Coahuila, Mexico (Rosa & Cevallos‐Ferriz, 1994), and ‘ Musa ’ cardiosperma , moved from the Musaceae to the Zingiberaceae (Manchester & Kress, 1993), found from the Maastrichtian/Danian boundary (c. 66 Ma) in Deccan, India (Jain, 1963).…”
Section: Methodsmentioning
confidence: 99%
“…Four additional studies of extinct species explore flowering plant evolution and phylogeny from fagalean inflorescences (Gandolfo et al., ), ericalean flowers (Crepet et al., ), zingiberalean monocot seeds (Smith et al., ), and Early Cretaceous seeds that are similar to those of basal living angiosperms (Friis et al., ). By comparing key morphological characters of fossil representatives to the pattern of structural features on the fagalean tree, Gandolfo et al.…”
mentioning
confidence: 99%
“…The inclusion of fossil seeds in morphological and combined morphological/nucleotide sequence analyses by Smith et al. () helps explain how different topologies from morphological and molecular data sets result from plesiomorphic characters shared by Musaceae, Zingiberaceae, Costaceae, and many zingiberalean fossils. This study emphasizes the pressing need for fossils to be incorporated into phylogenetic analyses, not only to place those fossils on the tree, but also to better understand morphological evolution, to establish character polarities, recognize homoplasy, and identify apparent data conflicts.…”
mentioning
confidence: 99%